(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The complex factual states arousing in connection with the publication agreements concluded in an international turnover constitute in the international civil law the source of the question of a demarcation line between the range of use of the competent law for the obligatory publishing relation (the obligation status) and the appropriate law for the evaluation of the copyright (the author’s status). The essence of the publication relations rests upon the use, in a definite scope, of the subjective copyright. Thus the sphere of the obligatory publishing relation is directly related to the sphere of these rights. While evaluating, according to the obligation status, the validity of the publication agreement and its effects in the relations between the parties, it is necessary to decide on the question whether there exists the copyright for a definite act of work, who is the subject of this right and what he is entitled to. In order to solve this problem the author’s status seems to be competent. It is the author’s status which deals With the questions connected with the admission, validity and effectiveness of disponsability of the "copyright (by means of transposition or charging with the subjective absolute right) accomplished within the framework of the publication agreement. Especially, the status defines the premises indispensable for the disposition (e.g. the disposition agreement, the publication of the manuscript of the act of work, the registration of the agreement and decides about the time in which it is concluded. Furthermore, the law competent for the copyright shapes the legal situation of the publisher as the subject acquired from the author of the right of an absolute nature. However, on the other hand, the consequences of certain activities evaluated by this right, e.g. the effects of inadmissibility of disposal of the copyright within the scope intended by the parties, or the lack of the copyright of the act of work being the subject of the agreement, undergo the obligation status. The status is also appropriate in the question of the declaration of wishes concerning the disposition of the copyright intended by the parties.